Fasilitas Pendidikan Dan Pelatihan Desain Grafis Di Pekanbaru Dengan Pendekatan Arsitektur Ekspresionis - Suci Rahmawati; Pedia Aldy; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The dynamics of graphic design activities are always closely related to technological developments and creative industry. In this digital era, people are more interested in visual information. Not a few of the people who are interested in pursuing the world of creative industries, one of them is graphic design. Graphic design is able to provide opportunities for the formation of new professions and create design ideas that support the progress of the creative industry. Pekanbaru is one of the right locations to built a Graphic Design Education and Training with the aim of attracting the interest of the community to develop creativity and skills in the field of graphic design. So that the community is able to create their potential to work and even compete competently. The Graphic Design Education and Training is a forum that accommodates inspiration and studies the science of graphic design as a skill, as well as a demand. Graphic design emphasizes expressive creativity, so Expressionist Architecture completes the identity and character of the building of Graphic Design Education and Training. Besides having educational goals, this design also displays visuals that are able to express imagination. The research methods used include field data collection, literature studies and empirical studies. The results of designed with the Infinity concept which adopted the form and meaning of the application principles from Expressionist Architecture. The attractive form of the building, the atmosphere of the form created by the use of building colors that inspire enthusiasm, and use of variative elements of material that play a role in conveying the message of the building's meaning. Keywords: Graphic Design, Expressionist Architecture, Infinity